Quantitative detection of cytokeratin 20 mRNA in urine samples as diagnostic tools for bladder cancer by real-time PCR - Guo, B.; Luo, C.; Xun, C.; Xie, J.; Wu, X.; Pu, J. (Experimental Oncology, 2009)
Aim: To determine and compare cytokeratin 20 (CK20) mRNA expression in urine of patients with transitional cell carcinomas of bladder (TCCB), urological benign diseases, and healthy volunteers. Methods: Taqman probe was designed according to the sequence of CK20 cloned gene. The quantitative PCR reaction system was optimized and evaluated. The CK20 mRNA level was screened by real-time polymerase chain reaction (RT-PCR) in 95 urine samples and analyzed according to the following parameters: urinary cytology, nuclear matrix protein 22 (NMP22) expression, tumor stage and grade. Results: For 60 TCCB patients urinary cytology was positive in 28 (46.7%), control group had no false-positive results (specificity 100%). CK20 expression was positive in RT-PCR of 51 cases (85%) of TCCB, but control group was positive in 2 cases (specificity 94.3%) with a cutoff value of crossover point (CT) = 30. Two methods have significant variation in sensitivity (p < 0.001), NMP22 expression was positive in 47 cases (78.3%), but control group was positive in 9 cases (specificity 85%). In the simultaneous evaluation of CK20 and NMP22 mRNA expression, there were 54 positive cases (90%). CK20 mRNA values in TCCB group (mean 27712.57 copies/µl) were significantly higher than in non-cancer disease urological group (mean 74.45 copies/µl) and control group (mean 8.47 copies/µl) (p < 0.001, p < 0.001, respectively). CK20 mRNA values increased gradually with higher tumor grade and stage: G1 differs significantly from G2 (p = 0.016); Tis/Ta differs significantly from T1–2 (p = 0.022). Conclusion: Our results indicate that CK20 mRNA expression could be regarded as a potential marker for TCCB. We demonstrated correlation between CK20 expression and the clinicopathologic features of TCCB (tumor stage and grade); simultaneous use of CK20 and NMP22 markers will elevate the sensitivity of the method. CK20 RT-PCR is a sensitive, quantitative, rapid and specific method to detect free cancer cells in the urine, and could be recommended for be wide application in the diagnostics of TCCB and evaluation of therapeutic effect.